Initial experience with combined BRAF and MEK inhibition with stereotactic radiosurgery for BRAF mutant melanoma brain metastases. Issue 4 (August 2016) - Patel, Bindiya G.; Ahmed, Kamran A.; Johnstone, Peter A.S.; Yu, Hsiang-Hsuan Michael; Etame, Arnold B.
Abstract : The combined use of the BRAF inhibitor dabrafenib and MEK inhibitor trametinib has been found to improve survival over dabrafenib alone. The management of melanoma brain metastases continues to present challenges. In this study, we report our initial experience in the management of melanoma brain metastases with stereotactic radiosurgery (SRS) with the use of BRAF and MEK inhibitors. We identified six patients treated with SRS for 17 brain metastases within 3 months of BRAF and MEK inhibitor administration. The median planning target volume was 0.42 cm 3 (range: 0.078–2.08 cm 3 ). The median treatment dose was 21 Gy (range 18–24 Gy). The median follow-up of all lesions from SRS was 10.6 months (range 5.8–28.5 months). One lesion was found to undergo local failure 21.7 months following SRS treatment. The median overall survival was 20.0 months (range 6.1–31.8 months) from the time of SRS treatment and 23.1 months (range: 12.1–30.9 months) from the date of BRAFi and MEKi administration. There was no evidence of increased nor unexpected toxicity with the two modalities combined. In this initial experience of melanoma brain metastases treated with BRAF and MEK inhibition with SRS, we find the two modalities can be combined safely. These outcomes should be assessed further in prospective evaluations.